اتجاهات معلمي الحلقة الثانية من التعليم الأساسي نحو استخدام الحاسوب في تعليم الرياضيات (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
تهدف الدراسة إلى الكشف عن اتجاهات معلمي الحلقة الثانية من التعليم الأساسي نحو استخدام الحاسوب في تعليم الرياضيات. ولتحقيق ذلك تم اعتماد المنهج الوصفي واستخدمت الاستبانة كأداة للإجابة عن أسئلة الدراسة، وقد تألفت من 30 عبارة تم توزيعها بعد التحقق من صدقها وثباتها على عيّنة عشوائية مؤلّفة من 33 معلماً ومعلمة من معلمي الحلقة الثانية من التعليم الأساسي في مدارس مدينة اللاذقية. وقد اقتصرت الاستبانة على محورين هما الموقف من استخدام الحاسوب والفائدة من ذلك في تعليم الرياضيات. وقد استخدم الوزن النسبي وتحليل التباين الأحادي للتحقّق من صحة الفرضيات والإجابة عن أسئلة الدراسة، وقد أظهرت نتائج الدراسة أنه لا توجد فروق ذات دلالة إحصائية بين متوسط استجابات أفراد العينة على محوري الاستبانة تبعاً لمتغيرات: الجنس، وعدد سنوات الخبرة في التدريس، واتباع دورة دمج التكنولوجيا في التعليم. وتبيّن أن أكثر فوائد استخدام الحاسوب في تعليم الرياضيات من وجهة نظر المعلمين هي مساهمته في تنويع أساليب التدريس وجعل التعلّم ممتعاً للطالب. The study aims to reveal the trends of teachers in the second stage of basic education about the use of computer in mathematics education. To achieve this, the descriptive method was adopted and a questionnaire was used as a tool to answer the questions of the study. It consisted of 30 items, and were distributed after verification of validity and persistence on a random sample of 33 teachers (males and females) in the second stage of basic education in the schools of Lattakia city. The questionnaire was limited to two parts: attitude to the computer use and its usefulness in mathematics education. The relative weight, and one-way ANOVA analysis were used to validate the hypotheses and answer the questions of the study, the results of the study showed that there were no significant differences between the average responses by respondents to a survey depending on variables: gender, and number of experience years in teaching and technology integration in education course. It was found out that most of the benefits of using computer in mathematics education from the teachers` viewpoint of is to diversify teaching methods and make learning fun for students.